A review on 4D additive manufacturing - The applications, smart materials & effect of various stimuli on 4D printed objects - Maidin, Shajahan; Kuek, Jin Wee; Sharum, Mohamad Afiq; Rajendran, Thavinnesh Kumar; Mohd Ali, Latifah; Ismail, Shafinaz (Penerbit UTM Press, 2023)
Additive Manufacturing, often known as 3D printing, is a process that uses a variety of materials to manufacture highly accurate items layer by layer. However, this technology has its limitations. One such limitation is the inability to print components larger than the printer's size due to the limited size of the build chamber. 4D additive manufacturing or 4D printing is an innovative development based on 3D printing that allows objects to be reshaped after printing, using stimuli-responsive materials that require external stimuli. This article present a review on 4D printing. Four databases, Google Scholar, ScienceDirect, IEEE Xplore, and Scopus database, were systematically searched for relevant review articles to identify and classify research studies. Specific keywords (4D printing, additive manufacturing, smart materials, stimuli, and application) were identified and used to guide the discovery of relevant studies. A total of 28 full articles were reviewed to study the applications of 4D printing, smart materials for 4D printing, as well as the effect of various stimuli on 4D printed objects. In conclusion, this review gives a summary of 4D printing and highlights its potential for revolutionizing manufacturing and further research is required to solve the limitations posed by this technology.